About difficult process of understanding - Gauck, Joachim (Genocidas ir rezistencija, 1999)
When secret service, party and state archives were opened for the public in 1990, revealing a wealth of partially unknown facts, many GDR citizens were deeply distrustful of their own system, and stimulated discussions about the creation of Soviet socialism and their personal relationship with it.